2013
DOI: 10.21831/amp.v1i1.2321
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Jenjang Pendidikan, Pelatihan, Dan Pengalaman Mengajar Terhadap Profesionalisme Guru Sma Muhammadiyah Di Kabupaten Kebumen

Abstract: Penelitian ini bertujuan untuk mengetahui hubungan jenjang pendidikan, pelatihan, dan pengalaman mengajar dengan profesionalisme guru SMA Muhammadiyah di Kabupa-ten Kebumen. Penelitian ini merupakan penelitian kuantitatif korelasional. Populasi dalam penelitian ini adalah seluruh guru SMA Muhammadiyah se-Kabupaten Kebumen, yang berjumlah 54 orang, sedangkan sampel penelitian adalah sejumlah 44 orang. Pengumpulan data meng-gunakan angket, dan analisis data menggunakan teknik analisis korelasi Pearson product mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 0 publications
2
4
0
4
Order By: Relevance
“…When the hours of flying or teaching hours of the teacher are more than 7 years, the level of professionalism in carrying out the learning is of course also better than teachers who have little teaching experience. This is in accordance with the results of research found by Eliyanto and Wibowo which stated that teaching experience has a positive and significant influence on teacher professionalism [5].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…When the hours of flying or teaching hours of the teacher are more than 7 years, the level of professionalism in carrying out the learning is of course also better than teachers who have little teaching experience. This is in accordance with the results of research found by Eliyanto and Wibowo which stated that teaching experience has a positive and significant influence on teacher professionalism [5].…”
Section: Discussionsupporting
confidence: 93%
“…Meanwhile, 22.22% of teachers already have a Master's certificate. Based on the results of research conducted by Eliyanto and Wibowo, it is stated that the level of education and training does not have a significant effect on teacher professionalism [5]. This shows that the level of education, both undergraduate and masters, has no effect on the quality of learning built by the teacher.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to mastering technology, groups of teachers with <10 years of teaching experience have the ability to develop student activities and tasks by involving the use of technology, being able to use computer applications in accounting learning (such as the use of MYOB Accounting software, Accurate software, and the application of the Village Financial System (Siskeudes) as well as skillfully using internet facilities to communicate with students. This is in accordance with the results of research conducted by Lin et al [10], Jang and Tsai [9], Ozudogru and Ozudogru [8], Jang and Tsai [16], Eliyanto and Wibowo [17] which stated that teaching experience affects teacher competency and TPACK mastery.…”
Section: Resultssupporting
confidence: 92%
“…Penerapan model pelatihan ini berdampak pada tingginya minat peserta terhadap pembelajaran BIPA, baik di dalam negeri maupun luar negeri. Hal itu mengakibatkan banyaknya pengajar dan kesiapan pengajar BIPA yang ada di Bengkulu untuk mengajar BIPA sehingga semakin kompetetif dan profesional dalam mengajar BIPA (Eliyanto & Wibowo, 2013;Rahmawati, 2015;Rakib dkk., 2016;Fitria dkk., 2019). Selain itu, profesional mengajar bahasa Indonesia akan semakin baik dan berkualitas serta lebih peduli terhadap pemakaian bahasa Indonesia.…”
Section: Pembahasanunclassified